N.N. Iordansky: about Social Education in the Soviet School (First Post-October Decade) - Pozdnyakov, Alexander Nikolaevich (Razvitie obrazovaniâ (Online), 2021)
The purpose of the article is to consider the views and assessments on the issues of social education of one of the prominent representatives of the Russian scientific and pedagogical community N.N. Iordansky, to trace their connection with the present. Research material. Scientific and pedagogical works of N.N. Iordansky became the material for the research. Research results and conclusions. One of the main directions of scientific and pedagogical activity of N.N. Iordansky was the issues of social education. The ideas and recommendations formulated by him were aimed at preparing a thinking and practically oriented graduate at school, capable and striving to independently acquire knowledge, determine his place in life and who is ready to successfully move along the intended path. They represent not only an important contribution to the history of pedagogical thought, but are also relevant for modern pedagogy.